Assistive technology products: a position paper from the first global research, innovation, and education on assistive technology (GREAT) summit. (4th July 2018) - Smith, Roger O.; Scherer, Marcia J.; Cooper, Rory; Bell, Diane; Hobbs, David A.; Pettersson, Cecilia; Seymour, Nicky; Borg, Johan; Johnson, Michelle J.; Lane, Joseph P.; Sujatha, S.; Rao, PVM; et al.
Abstract: This paper is based on work from the Global Research, Innovation, and Education on Assistive Technology (GREAT) Summit that was coordinated by WHO's Global Cooperation on Assistive Technology (GATE). The purpose of this paper is to describe the needs and opportunities embedded in the assistive product lifecycle as well as issues relating to the various stages of assistive product mobilization worldwide. The paper discusses assistive technology product terminology and the dangers of focusing on products outside the context and rolling out products without a plan. Additionally, the paper reviews concepts and issues around technology transfer, particularly in relation to meeting global needs and among countries with limited resources. Several opportunities are highlighted including technology advancement and the world nearing a state of readiness through a developing capacity of nations across the world to successfully adopt and support the assistive technology products and applications. The paper is optimistic about the future of assistive technology products reaching the people that can use it the most and the excitement across large and small nations in increasing their own capacities for implementing assistive technology. This is expressed as hope in future students as they innovate and in modern engineering that will enable assistive technology to pervade all corners of current and potential marketplaces. Importantly, the paper poses numerous topics where discussions are just superficially opened. The hope is that a set of sequels will follow to continue this critical dialog. Implications for Rehabilitation: Successful assistive technology product interventions are complex and include much more than the simple selection of the right product. Assistive technology product use is highly context sensitive in terms of an individual user's environment. The development of assistive technology products is tricky as it must be contextually sensitive to the development environment and market as well. As a field we have much to study and develop around assistive technology product interventions from a global perspective.